Implementasi Metode Hypnoteaching Pada Pembelajaran Tata Bahasa Arab: Studi Fenomenologi Pada SMA Islam Sunan Gunung Jati Tulungagung - Moh Ikhsani; Choiruddin Choiruddin (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Hypnoteaching is a new learning method in Arabic learning. Start from the development of hypnoteraphy in a variety of functions and uses such as health, psychological to the field of education which is then called hypnoteaching. This method is a learning method that uses positive suggestions to reach students' subconscious. The innovation of learning methods with hypnoteaching can make Arabic learning more enjoyable. This research is a literature study that seeks to find the literatures that are in accordance with the theme of the discussion then analyzed by descriptive analysis. The results showed that hypnoteaching fulfilled the requirements as a new method in learning Arabic. This is one of the innovations in Arabic learning methods that can be used today. Because this method maximizes students' subconscious, so learning can achieve maximum results with fun learning.